Claims and reasons about mild COVID-19 in children - S. Falahi; A. Abdoli; A. Kenarkoohi (New Microbes and New Infections, 2021)
The elderly form the main risk group in the coronavirus disease 2019 (COVID-19) pandemic, and age is recognized as a major risk factor for the severity of infection and mortality of COVID-19. The severity of the infection in children is milder than in adults. Although the pathophysiology of COVID-19 is not fully understood, several possible factors and mechanisms have been suggested for the lower severity of infection in children.